The Relationship Between High-Sensitivity C-Reactive Protein (hs-CRP) and Diastolic Dysfunction in Geriatrics Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Muhammad Hadi Wijaya; Ali Ghanie; Nur Riviati; Mgs. Irsan Saleh (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Systemic inflammation associated with high hs-CRP levels constitutes one pathway through which diastolic dysfunction develops in older adults. This study aims to determine the relationship between high-sensitivity c-reactive protein (hs-CRP) and diastolic dysfunction in older adults at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This research is an observational analytical study using a cross sectional design. The research was conducted at the geriatrics polyclinic at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia from June to August 2023. A total of 65 people took part in this study. The relationship between hs-CRP and diastolic dysfunction was analyzed using SPSS version 25, univariate and bivariate. Results: Hs-CRP had a significant relationship with diastolic dysfunction on a numerical scale (p=0.012), with a median value of 1.6 mg/dL in subjects with diastolic dysfunction and 0.9 mg/dL in subjects without diastolic dysfunction. On the categorical scale, the hsCRP less than 1 mg/dL group found nine subjects (23.7%) with diastolic dysfunction and 14 subjects (51.9%) without diastolic dysfunction, the hsCRP 1-3 mg/dL group found 21 subjects (55.3%) with diastolic dysfunction and 12 subjects (44.9%) without diastolic dysfunction, in the hsCRP more than 3 mg/dL group (p=0.026) there were eight subjects (21.1%) with diastolic dysfunction and one subject (3.7%) without dysfunction diastolic. Conclusion: There is a significant relationship between hsCRP and left ventricular diastolic dysfunction in geriatrics patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.